Women of war, women of woe: Joshua and Judges through the eyes of nineteenth-century female biblical interpreters - Taylor, Marion Ann; De Groot, Christiana (William Eerdmans Publishing Company, 2016)
This volume gathers the writings of thirty-five nineteenth-century women on the stories of women in Joshua and Judges. Recovering and analyzing neglected works by Elizabeth Cady Stanton, Harriet Beecher Stowe, and many others, Women of War,Women of Woe illuminates the biblical text, recovers a neglected chapter of reception history, and helps us understand and apply Scripture in our present context. The stories of Rahab, Deborah, Jael, Delilah, Manoah's wife, Achsah, Jephthah's daughter, and the Levite's concubine raised thorny questions for these female biblical interpreters -- questions that they addressed candidly in their writings. Could a Victorian woman use her intelligence to negotiate like Rahab? Was the seemingly well-educated Deborah an appropriate role model? Or did Jephthah's daughter more correctly model a pious woman's life as she submitted to her father's vow? The voices collected in this book offer thoughtful reflection on and responses to these questions and more.